Structure of the three β-tubulin-encoding genes of the unicellular alga, Polytomella agilis - Conner, Timothy W.; Thompson, Michael D.; Silflow, Carolyn D. (Gene, 1989)
The quadriflagellate, unicellular, colorless alga, Polytomella agilis, contains several distinct microtubule arrays. To study the genetic basis of microtubule heterogeneity in P. agilis, we characterized its tubulin(Tub)-encoding genes ( tub). The three β tub genes detected in blots of P. agilis DNA were isolated from a genomic library. The structure and organization of the genes were examined by restriction mapping and nucleotide (nt) sequencing. S1 nuclease protection studies showed that all three genes are expressed. The predicted amino acid (aa) sequences are more than 98% conserved with the Chlamydomonas reinhardtii and Volvox carteri β-Tubs, underscoring the close phylogenetic relationship of these species. Evolutionary divergence among the P. agilis genes is demonstrated by differences in intron number, nt sequences in noncoding regions, and silent nt substitutions in the coding regions. However, the proteins encoded by the β1 and β3 tub genes are identical; the β2 gene product differs by one conservative aa substitution. These results are in striking contrast to the C-terminal aa diversity reported within β tub gene families in animal, higher plant and fungal systems. The data support the hypothesis that those tub genes whose products assemble into axonemal microtubules are subject to strong selection against nt substitutions causing aa replacements.